The Treaty of Berlin 1878: Implications for Muslims Migration in Bosnia-Herzegovina Before World War 1 - Mat Enh, Azlizan; Mansor, Suffian; Abd. Razak, Mohamad Rodzi (Journal of Al-Tamaddun, 2022)
The intervention of the great powers in the Bosnian-Herzegovina conflict of 1875-1878 led the Turkish government to sign the Treaty of Berlin of 1878. One of the terms of the Treaty of Berlin was to put the administration of Bosnian-Herzegovina under the auspices of the mandate of the Austrian-Hungarian government. From this point onwards, the migration process in Bosnia-Herzegovina is reflected in its population, especially Muslims. This article examines the implications of the Treaty of Berlin on issues that led to the emigration of Muslims from Bosnia-Herzegovina to other regions of the Turkish Empire before the outbreak of World War 1. The analysis of primary data was used on the British records from its embassy in Bosnia- Herzegovina. The study found that religious issue was a crucial factor in the migration process happened in Bosnia-Herzegovina. The migration process intensified after Bosnia-Herzegovina was formally announced to be put under the Austrian-Hungarian administration in 1908.